Sistem Pengenalan Kata dengan Menggunakan Linear Predictive Coding dan Nearest Neighbor Classifier - , Thiang; Saputra, Hadi (Institute of Research and Community Outreach, 2005)
This paper describe about the development of word recognition system by using a voice matching approach, which will match between reference voice spectrum and unknown voice spectrum. This designed system is limited to recognize a voice, which only consists of one word. There are five words, which will be recognized in this system. They are